Age-related reproductive performance of the Adélie Penguin, a long-lived seabird exhibiting similar outcomes regardless of individual life-history strategy - Kappes, Peter; Dugger, Katie; Lescroël, Amélie; Ainley, David; Ballard, Grant; Barton, Kerry; Lyver, Philip; Wilson, Peter (Zenodo, 2020)
1. Age-related variation in reproductive performance in long-lived iteroparous vertebrate species is common, with performance being influenced by within-individual processes, such as improvement and senescence, in combination with among-individual processes, such as selective appearance and disappearance. Few studies of age-related reproductive performance have compared the role of these drivers within a metapopulation, subject to varying degrees of resource competition. 2. We accounted for within- and among-individuals changes among known-aged Adélie penguins (Pygoscelis adeliae) during 17 years (1997 to 2013), at three clustered colonies of disparate size, to understand patterns in age-related reproductive success during early and late adulthood. 3. Age at first reproduction (AFR) was lowest, and number of breeding attempts highest, at the largest colony. Regardless of AFR, success improved with early post-recruitment experience. For both oldest and youngest recruitment groups, peak performance occurred at the end of their reproductive lifespan indicating a possible cost of reproduction. Intermediate recruitment groups reached peak performance in their mid-reproductive lifespan and with intermediate breeding experience, before decreasing. Breeding success was lowest for the initial breeding attempt regardless of AFR, but we observed subsequent variation relative to recruitment age. Gaining experience by delaying recruitment positively influenced reproductive performance early in the reproductive lifespan, and was most evident for the youngest breeders. Oldest recruits had the highest initial and peak breeding success. Differences in AFR resulted in tradeoffs in reproductive lifespan or timing of senescence but not in the overall number of breeding attempts. 4. Patterns differed as a function of colony size, and thus competition for resources. Early life improvement in performance at the larger colonies was primarily due to within-individual factors and at the largest colony, AFR. Regardless of colony size ...